1998
DOI: 10.1039/a803999b
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ionic liquids as novel media for ‘clean’ liquid–liquid extraction

Abstract: The partitioning of simple, substituted-benzene derivatives between water and the room temperature ionic liquid, butylmethylimidazolium hexafluorophosphate, is based on the solutes' charged state or relative hydrophobicity; room temperature ionic liquids thus may be suitable candidates for replacement of volatile organic solvents in liquid-liquid extraction processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
1,499
1
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,199 publications
(1,521 citation statements)
references
References 8 publications
(11 reference statements)
9
1,499
1
12
Order By: Relevance
“…34−36 These studies revealed that the nature of RTILs is more complicated than conventional solvents due to the presence of structural heterogeneity of the microenvironment in RTILs, which affects the solvation and rotational dynamics and other processes of the solute in RTILs. 16,29,33 Furthermore, molecular dynamics (MD) simulation studies have indicated that RTILs based on the 1-alkyl-3-methylimidazolium cation ([C n mim] + ) with alkyl chains C 4 and longer are spatially heterogeneous, 37−41 where two types of structural domains with alkyl chains of C 4 or longer in the ionic liquid were expected. Nonpolar domains arising from aggregation of the alkyl chains are formed mainly through the weak essentially van der Waals interactions, and polar domains arising from charge ordering of the anions and imidazolium rings of the cations are formed through the strong electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…34−36 These studies revealed that the nature of RTILs is more complicated than conventional solvents due to the presence of structural heterogeneity of the microenvironment in RTILs, which affects the solvation and rotational dynamics and other processes of the solute in RTILs. 16,29,33 Furthermore, molecular dynamics (MD) simulation studies have indicated that RTILs based on the 1-alkyl-3-methylimidazolium cation ([C n mim] + ) with alkyl chains C 4 and longer are spatially heterogeneous, 37−41 where two types of structural domains with alkyl chains of C 4 or longer in the ionic liquid were expected. Nonpolar domains arising from aggregation of the alkyl chains are formed mainly through the weak essentially van der Waals interactions, and polar domains arising from charge ordering of the anions and imidazolium rings of the cations are formed through the strong electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the second approach, the IL was injected into a preheated aqueous sample. The 1-decyl-3-methylimidazolium tetrafluoroborate ([C 10 MIM + ][BF 4 − ]) IL was used in the extraction of the derivatized herbicide glyphosate (Gly-FMOC) and its major metabolite, aminomethylphosphonic acid (AMPA-FMOC) in real water samples. Although both methods exhibited enrichment factors above 50, recoveries between 92 and 99%, and RSD values below 7%, the second approach was 5 min faster due to preheating of the aqueous sample.…”
Section: Temperature-assisted Il-dllmementioning
confidence: 99%
“…1-5 Such environmental-friendly properties make ILs relatively benign solvents for cleaner processes to minimize toxic chemical wastes which have become a priority for chemical industries. 6 Room temperature ILs have been used in various applications such as replacing conventional organic solvents in organic synthesis, 7 solvent extractions, 8 electrochemical reactions, 9,10 liquid-liquid extractions, 11 and in enzymatic reactions. 12 In addition, analytical applications of ILs such as their use as buffers in capillary electrophoresis, 13 as stationary phases in gas chromatography 14,15 as well as high performance liquid chromatography, 16 and enhancement of sensitivity in thermal lens measurement have also been investigated.…”
Section: Introductionmentioning
confidence: 99%